(untitled) (Experimental biology, 2015)
Educational, industrial and diploma practices given in fish breeding farms are very important for professional establishment of “6М080400 – Fish industry and commercial industry” specialty students. During the practices students have got methods of fish investigation and obtain necessary knowledge for degree diploma doing.